PENGARUH KUALITAS NETWORK & TARIF SIMPATI TERHADAP LOYALITAS PEGAWAI PEMERINTAHAN KABUPATEN ACEH SINGKIL - Ardiansyah Putra Ramadhan; Amrin Fauzi; Endang Sulistya Rini (Universitas Islam Negeri Sumatera Utara Medan, 2016)
Cellular telecommunication is a cellular operator company which has grownrapidly amidst the tight competition among the cellular operator companies inIndonesia. Realizing that it is very crucial to keep the customers and to find morepotential customers, the company strives to upgrade network quality and adjust fare. Thecompany’s most potential customers are employees. The formulation of the problem wasto what extent the influence of network quality and simPATI’s fare on loyalty. The aimof this research was to know and to analyze the influence of network quality andsimPATI’s fare on loyalty. The research was descriPT.ive quantitative;. The data wereprocessed by using SPSS version 16 software. The hypothesis was tested by usingmultiple linear regression analysis, F test and t test in order to know the influence ofindependent variables on the dependent variables in the liability of 95% (α =0.05). Thedata were collected by questionnaires. The result of the research from the simultaneoustest showed that the network quality and simPATI’s fare had positive influence on loyalty.The variables of the network quality played an important role in determining the loyaltyof Aceh Singkil government employee, compared with the variables of simPATI’s fare.The variables of network quality and simPATI’s fare were able to explain their role ingiving the satisfaction of the pre-paid Telkomsel consumers 35,2% to the Aceh Singkilgovernment employees, and the rest (64,8%) was explained by the other variables whichwere not studied in this research. The conclusion of this research was that networkquality and simPATI’s fare had significant influence on the Aceh Singkil governmentemployees.Keywords: Kualitas, Tarif dan Loyalitas.